Pengaruh Peran Kepemimpinan Dan Intellectual Capital Terhadap Kinerja Guru Yang Di Moderasi Oleh Motivasi Berprestasi Pada Yayasan Wakaf Merdeka Perguruan Nasional Makassar - Husnul Khatimah; Edi Jusriadi; M yusuf Alfian Rendra Angoro KR; Muhammad Rusydi (Jurnal Mirai Management, 2023)
This research aims to determine and analyze the influence between leadership and leadership variablesintellectual capital on achievement motivation, knowing and analyzing leadership,intellectual capital and achievement motivation on teacher performance, knowing and analyzing the influence of leadership andintellectual capital on teacher performance moderated by achievement motivation. This study used primary data through a questionnaire of 98 respondendendents and used the entire population as a sample. This research was conducted for 2 months and started from November 2022 to December 2022. The research method used is a quantitative approach which emphasizes analysis of numerical data. processed by statistical methods, with data analysis techniquesPartial Last Square Smart-PLS. The results of the study show that: [1] Leadership (X1) has a positive and significant effect on achievement motivation (Y1), [2]Intellectual Capital (X2) has a positive but not significant effect on Achievement Motivation (Y1), [3] Achievement Motivation (Y1) has a positive and significant effect on Teacher Performance (Y2), [4] Leadership (X1) has a positive and significant effect on Teacher Performance (Y2 ), [5]Intellectual Capital (X2) has a positive but not significant effect on Teacher Performance (Y2), [6] Achievement Motivation (Y1) has a negative and insignificant effect mediating the relationship between Leadership (X1) and Teacher Performance (Y2), [7] Achievement Motivation (Y1) positive effect but not significantly mediate the relationship betweenIntellectual Capital (X2) and Teacher Performance (Y2). Kata Kunci: Leadership, Intellectual Capital, Achievement Motivation, Teacher Performance